EFEKTIVITAS DESTINASI WISATA INDOOR DALAM MENGANTISIPASI PERUBAHAN MUSIM DAN MENJAGA CITRA PARIWISATA YOGYAKARTA - Ajie Wicaksono; Suradi; Anton Triyantoro (JURNAL MATA PARIWISATA, 2026)
The tourism sector in Yogyakarta is highly vulnerable to seasonal changes and extreme weather due to its heavy reliance on outdoor attractions, which negatively impacts destination image. This study aims to examine the effectiveness of indoor tourism destinations in mitigating the risks of extreme weather and maintaining Yogyakarta's tourism image. A quantitative explanatory approach was employed using Structural Equation Modelling (SEM) based on Partial Least Squares (PLS). Data was collected from a sample of 400 domestic tourists who visited at least two indoor destinations in Yogyakarta during the peak rainy season. The analysis reveals that the effectiveness of indoor facilities and weather anticipation capacity directly and significantly affect tourism image with path coefficients of β = 0.285 and β = 0.240, respectively. The combination of indoor facilities, weather mitigation, and tourist experience explains 71.5% of the variance in destination image (R² = 0.715). Furthermore, tourist experience acts as a significant partial mediator between indoor facilities and tourism image (β = 0.171), and between weather anticipation and tourism image (β = 0.157). In conclusion, developing climate-responsive indoor infrastructure, combined with high-value tourist experiences, is a fundamental strategy for building regional tourism resilience.